Antioxidative Activity Evaluation of High Purity and Micronized Tartary Buckwheat Flavonoids Prepared by Antisolvent Recrystallization - Yanjie Liu; Xiaoyu Sui; Xiuhua Zhao; Siying Wang; Qilei Yang (Foods, 2022)
Tartary buckwheat, a healthy food, is associated with a reduced risk of certain human chronic diseases. However, the bioactive component flavonoids in Tartary buckwheat have poor solubility and low absorption in vivo. To improve these points, 60.00% Tartary buckwheat total flavonoids (TFs) were obtained by ethanol refluxing method, which were purified and micronized by antisolvent recrystallization (ASR) using methanol as a solvent and deionized water as an antisolvent. By using High Performance Liquid Chromatography (HPLC) and electrospray ionized mass spectrometry (ESI-MS), the main flavonoid in pure flavonoids (PF) were rutin (RU), kaempferol-3-O-rutinoside (KA) and quercetin (QU); the content of TF is 99.81% after purification. It is more worthy of our attention that micronized flavonoids contribute more to antioxidant activity because of good solubility. These results provide a theoretical reference for the micronization of other flavonoids.